(untitled) (Global Journal of Science Frontier Research, 2013)
The statement about the property of some definite thing is not usually the only one. The difference between the stated property and the property of such a definite thing is one type of information rheology. Its origin is that the interaction of a definite thing with other things is incomplete. Based on the definition of customarily-called information and its mathematical expression, this paper points out that information rheology certainly exists. It gives us a caution that information is not necessarily conclusive, and not likely to correspond to definite things. Information is not the criterion, but practice is the sole one for testing truth. It is certain that to study customarily-named information by bringing it to the height of ontology is not promising. Also, the attempt to justify information is hard to be realized